Ni/Ce as a Cobalt-Free Coating Alternative for SOEC Interconnects - Ahmed, Tola; Abualdeber, Adam (My University, 2026)
Ferritic stainless steels are widely used as interconnect materials in solid oxide electrolysis cells (SOECs), but oxide-scale growth and chromium evaporation can reduce their durability. Although Co-based coatings effectively suppress chromium volatilisation, concerns regarding cobalt supply, cost, and sustainability motivate the development of cobalt-free alternatives. This thesis evaluates Ni/Ce as a cobalt-free alternative to Co/Ce coatings on Crofer 22 APU and IM1 ferritic stainless steels. Coated and uncoated specimens were exposed in air containing 3% H2O at 600 and 700 ◦C for up to 504 h. Oxidation behaviour, chromium evaporation, and oxide-scale development were investigated using mass-change measurements, the denuder technique, UV–Vis spectrophotometry, and SEM/EDX analysis. Dual-atmosphere exposures were also performed on IM1 at 600 ◦C. Both coatings substantially reduced chromium evaporation compared with the corresponding uncoated materials. Co/Ce provided the strongest overall chromiumretention performance. The greatest improvement was observed for Co/Ce-coated Crofer 22 APU after 504 h at 700 ◦C, for which the cumulative chromium release was approximately 20.7 times lower than for the uncoated material. Ni/Ce also effectively suppressed chromium evaporation and showed promising performance as a cobalt-free coating. Ni/Ce-coated IM1 and Crofer 22 APU exhibited broadly similar oxidation behaviour, chromium-evaporation trends, and oxide-scale development, indicating that the coating had a strong influence on the degradation response under the investigated conditions. Microstructural analysis revealed clear effects of coating chemistry and exposure environment on oxide-scale development. Under dual-atmosphere conditions, Co/Cecoated IM1 exhibited the lowest local reaction-zone thickness and retained a compositionally distinct Co-rich outer region. In contrast, Ni/Ce-coated IM1 developed a thicker and more heterogeneous oxide/coating region, with Fe extending through much of the reaction zone. Overall, Ni/Ce demonstrated potential as a cobalt-free coating for SOEC interconnects, but it did not provide the same overall level of protection as Co/Ce, particularly at 700 ◦C and under dual-atmosphere conditions. The results also indicate that lower-cost ferritic stainless steels such as IM1 may provide performance approaching that of conventional interconnect alloys when combined with a suitable protective coating.
Keywords: Solid oxide electrolysis cell; Ferritic stainless steel; interconnect; chromium evaporation; oxidation; Co/Ce coating; Ni/Ce coating; dual-atmosphere corrosion